Diagnostic accuracy of WHO screening criteria to guide lateral-flow lipoarabinomannan testing among HIV-positive inpatients: A systematic review and individual participant data meta-analysis. Issue 1 (July 2022) - Dhana, Ashar; Hamada, Yohhei; Kengne, Andre P; Kerkhoff, Andrew D; Broger, Tobias; Denkinger, Claudia M; Rangaka, Molebogeng X; Gupta-Wright, Ankur; Fielding, Katherine; Wood, Robin; Huerga, Helena; Rücker, Sekai Chenai Mathabire; et al.
Highlights: WHO screening criteria and alternative screening tools to guide AlereLAM and FujiLAM testing have suboptimal diagnostic accuracy in HIV-positive medical inpatients. Thus, AlereLAM testing should be implemented in all HIV-positive medical inpatients alongside routine molecular diagnostic testing. If commercially available, FujiLAM could substantially improve detection of tuberculosis. Summary: Background: WHO recommends urine lateral-flow lipoarabinomannan (LF-LAM) testing with AlereLAM in HIV-positive inpatients only if screening criteria are met. We assessed the performance of WHO screening criteria and alternative screening tests/strategies to guide LF-LAM testing and compared diagnostic accuracy of the WHO AlereLAM algorithm (WHO screening criteria followed by AlereLAM if screen positive) with AlereLAM and FujiLAM (a novel LF-LAM test) testing in all HIV-positive inpatients. Methods: We searched MEDLINE, Embase, and Cochrane Library from Jan 1, 2011 to March 1, 2020 for studies among adult/adolescent HIV-positive inpatients regardless of tuberculosis signs and symptoms. The reference standards were (1) AlereLAM or FujiLAM for screening tests/strategies and (2) culture or Xpert for AlereLAM/FujiLAM. We determined proportion of inpatients eligible for AlereLAM using WHO screening criteria; assessed accuracy of WHO criteria and alternative screening tests/strategies to guide LF-LAM testing; compared accuracy of WHO AlereLAM algorithm with AlereLAM/FujiLAM testing in all; and determined diagnostic yield of AlereLAM, FujiLAM, and Xpert MTB/RIF (Xpert). We estimated pooled proportions with a random-effects model, assessed diagnostic accuracy using random-effects bivariate models, and assessed diagnostic yield descriptively. Findings: We obtained data from all 5 identified studies ( n  = 3, 504). The pooled proportion of inpatients eligible for AlereLAM using WHO criteria was 93% (95%CI 91, 95). Among screening tests/strategies to guide LF-LAM testing, WHO criteria, C-reactive protein (≥5 mg/L), and CD4 count (<200 cells/μL) had high sensitivities but low specificities; cough (≥2 weeks), hemoglobin (<8 g/dL), body mass index (<18.5 kg/m 2 ), lymphadenopathy, and WHO-defined danger signs had higher specificities but suboptimal sensitivities. AlereLAM in all had the same sensitivity (62%) and specificity (88%) as WHO AlereLAM algorithm. Sensitivity of FujiLAM and AlereLAM was 69% and 48%, while specificity was 88% and 96%, respectively. In 2 studies that collected sputum and non-sputum samples for Xpert and/or culture, diagnostic yield of sputum Xpert was 40–41%, AlereLAM was 39–76%, and urine Xpert was 35–62%. In one study, FujiLAM diagnosed 80% of tuberculosis cases (vs 39% for AlereLAM), and sputum Xpert combined with AlereLAM, urine Xpert, or FujiLAM diagnosed 61%, 81%, and 92% of all cases, respectively. Interpretation: WHO criteria and alternative screening tests/strategies have limited utility in guiding LF-LAM testing, suggesting that AlereLAM testing in all HIV-positive medical inpatients be implemented. Routine FujiLAM may improve tuberculosis diagnosis. Funding: None.